2014
DOI: 10.1007/s00018-014-1790-1
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of hemeoxygenase-1 in gastrointestinal diseases

Abstract: Disorders and diseases of the gastrointestinal system encompass a wide array of pathogenic mechanisms as a result of genetic, infectious, neoplastic, and inflammatory conditions. Inflammatory diseases in general are rising in incidence and are emerging clinical problems in gastroenterology and hepatology. Hemeoxygenase-1 (HO-1) is a stress-inducible enzyme that has been shown to confer protection in various organ-system models. Its downstream effectors, carbon monoxide and biliverdin have also been shown to of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 149 publications
(226 reference statements)
0
44
0
Order By: Relevance
“…Of note, HO-1 overexpression can be applied in multiple clinical conditions, such as organ transplantation, acute kidney injury, hypertension and atherosclerosis (914). Importantly, HO-1 is known to exhibit cytoprotective, anti-inflammatory, anti-proliferative, antioxidant and anti-apoptotic activities, making it a promising therapeutic target for the treatment of inflammatory diseases of the gastrointestinal system (15). Panhematin leads to the rapid induction and activation of pancreatic HO-1, and has potential for use in the treatment of human pancreatitis (16).…”
Section: Introductionmentioning
confidence: 99%
“…Of note, HO-1 overexpression can be applied in multiple clinical conditions, such as organ transplantation, acute kidney injury, hypertension and atherosclerosis (914). Importantly, HO-1 is known to exhibit cytoprotective, anti-inflammatory, anti-proliferative, antioxidant and anti-apoptotic activities, making it a promising therapeutic target for the treatment of inflammatory diseases of the gastrointestinal system (15). Panhematin leads to the rapid induction and activation of pancreatic HO-1, and has potential for use in the treatment of human pancreatitis (16).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported in rat models of reflux esophagitis that pretreatment with antioxidative isorhamnetin decreased esophageal lesion score reducing MDA levels, possibly due to the upregulation of the esophageal HO-1 expression [50]. Additionally, in cultured esophageal epithelial cells (EEC), it has been observed that euptailin prevented indomethacin-induced cytotoxicity and upregulated HO-1 expression due to nuclear translocation of transcription factor nuclear factor erythroid 2related factor 2 (Nrf2) and the activation of extracellular signal-regulated kinases (ERKs) and phosphatidylinositol-3kinase (PI3K)/Akt signaling [24,51]. However, possible involvement of HO and CO and their possible interaction in the regulation of oxidative stress in the esophageal mucosa requires further investigations.…”
Section: Co and Oxidation Within Thementioning
confidence: 99%
“…Moreover, this protein was localized in sinusoidal cells of the rat's liver [21]. Interestingly, pharmacological inhibition of HO by zinc protoporphyrin IX resulted in the attenuation of vasoactive intestinal polypeptide-(VIP-) induced low esophageal sphincter relaxation implying that this enzymatic protein contributes to the regulation of the motor activity of the upper GI tract [22][23][24].…”
Section: Introductory Notesmentioning
confidence: 99%
“…CO, one of the products of HO-1, exhibits anti-inflammatory activity (by downregulation of proinflammatory cytokines, as for instance interleukin-1b (IL-1b), IL-6, and tumor necrosis factor-a, TNF-a), antiapoptotic effects (by downregulation of caspases activation), and anti-proliferative effects by increasing cGMP levels, as reviewed by Ryter et al [45]. Moreover, CO exerts antioxidant actions in several experimental models [46][47][48][49].…”
Section: Antioxidant Capacity Of Phloretin On Brain Cellsmentioning
confidence: 99%